Osteochondroma Involving the Ramus of the Mandible: An Unusual Location - Pakki Suresh Kumar; Dola Srinivasa Rao; Swapna Manepalli; Ajit Damera; Jai Kiran Killada (Hindawi Limited, 2020)
Osteochondroma (OC) is considered the most common tumor of the axial skeleton, although it is relatively uncommon in the craniofacial region. The present case describes an atypical case of OC in the posterior border of the ramus of the mandible. To the best of our knowledge, only one case has been reported till now in this region. A 35-year-old male patient reported with a complaint of swelling over the left middle one-third of the face and limited mouth opening for six years. Panoramic radiograph (PR) and paranasal sinus (PNS) view showed a well-defined radiopacity located in this region. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed a characteristic mushroom-shaped outgrowth from the inner surface of the ramus of the mandible. The patient was treated with osteotomy, with the cut made at the angle of the mandible. Histopathological examination revealed features suggestive of OC. Subsequently, the patient was able to open his mouth, and there was no evidence of recurrence or postoperative complications in the one-year follow-up.